Perancangan Website Sistem Informasi Penunjuk Arah Wifi id Wilayah Semarang - Nur Hakim, Fitro; Restu Nugraha, Septianto (Informatika: Jurnal Teknik Informatika dan Multimedia, 2023)
Wifi@id internet is a public service of technology-based Wifi / Hotspot provided by TELKOM Group. WiFi@id wifi is a promising business for the company because of its CDMA business declined previously lived. Problems that occur at this time is the lack of information between users with id being wifi locations. It causes the user to access the wifi en manual are based on the location, while the location of wifi id contained in the shared location. Design website information systems and route search nearby directions wifi @ id is located. This website system enables users to find the location nearest wifi id with the position where the user is located. This mapping information design using a model of the development of the SDLC (system development life cycle), namely the development of a model system in stages starting from the analysis, the initial design, through implementation phase object-oriented programming is UML (unified modeling language), the data collection techniques namely observation and interviews. Conclusion of this website information system that can manage data wifi, managing user data, and know the location of the user's location.